A section-sampling design to assess zooplankton distribution in a highly complex hydrographic region (sw Atlantic Ocean, 34-41°s): insights for a new time series? - Cepeda, Georgina Daniela (2012)
Regular fish stock assessment cruises could provide a proper data platform to sample zooplankton. It is essential, however, that adequate sampling designs should be developed for each area so that zooplankton features may be accurately described with minimum sampling effort. On the Northern Argentine Continental Shelf (NACS, 34-41°S), a sectioned-sampling design (18 samples distributed in 4 sections) associated with E. anchoita stock estimation cruises was implemented to provide a rapid and reliable survey of zooplankton distribution in relation to the physical environment. The results obtained were similar to those registered in previous studies based on exhaustive sampling. We suggest that a new zooplankton time series covering this broad área be established, based on this sampling design, to contribute to the knowledge of the variability of zooplankton populations and their relation to fishery resources.